An Evidence-based Model of Teacher Engagement in Indonesia: Indonesian Teacher Engagement Index (ITEI) - ., Sasmoko; Indrianti, Yasinta; Khan, Aqeel; Fadila Amin, Nor (International Journal of Engineering and Technology, 2018)
Educational transformation can occur when teachers are directly involved in seeking change through self-diagnostic measurements to have a clear picture of Indonesian teachers’ capacity as a teacher, professional and Indonesian character educator. The instrument discussed in this research is the Indonesian Teacher Engagement Index (ITEI). This research is the result of the literature review to produce the ITEI model. The research used Neuroresearch method with an exploratory stage through journal study and focus group discussion. The result of the research found that there is a teacher engagement model that is suitable for the characteristics of teachers in Indonesia.